2022
DOI: 10.1161/strokeaha.121.036894
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Maintaining Brain Health: The Role of Stroke Risk Factors Unique to Elderly Women

Abstract: Stroke risk and prevalence increase with advanced age and women tend to be older than men at the time of their first stroke. Advanced age in women confers unique stroke risks that are beyond reproductive factors. Previous reviews and guidelines have largely focused on risk factors specific to women, with a predominant focus on reproductive factors and, therefore, younger to middle-aged women. This review aims to specifically describe stroke risk factors in elderly women, the population of women where the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 122 publications
(151 reference statements)
1
0
0
Order By: Relevance
“…Interestingly, when we conducted separate analyses by sex, we found that atrial fibrillation was a significant factor contributing to vascular risk in women, but not in men. This observation is consistent with the existing literature ( 24 , 25 ).…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, when we conducted separate analyses by sex, we found that atrial fibrillation was a significant factor contributing to vascular risk in women, but not in men. This observation is consistent with the existing literature ( 24 , 25 ).…”
Section: Discussionsupporting
confidence: 94%